The Association Of Social Media Motivation, Trust, Culture Restraint And Relationship Benefit Towards Online Relationship Commitment - Hatamleh, Islam Habis Mohammad (2021)
The present study examined the effect of social media motivation on relationship benefits and online relationship commitment and considered the moderating effect of cultural restraint on the relationship between social media motivation, relationship benefits and online relationship commitment. The study also explored the influence of relationship benefits and trust on online relationship commitment. A total of 384 young adults in Jordan were recruited for this study.